Acute Thrombocytopenia, Leucopenia, and Multiorgan Dysfunction: The First Case of SFTS Bunyavirus outside China? - Srdjan Denic; Joumana Janbeih; Suresh Nair; Walter Conca; Waheed Uz Zaman Tariq; Suhail Al-Salam (Case Reports in Infectious Diseases)
We report a 57-year-old man with acute thrombocytopenia, leucopenia, and multiorgan dysfunction. Patient was from North Korea and was temporarily working in Dubai, United Arab Emirates, when he fell ill in March 2009. At the same time and unknown to us, many patients with similar clinical manifestations were admitted to hospitals in China. The Chinese cases—identified between March and July 2009—were recently reported to have been infected with a tick-born strain of bunyavirus, a new disease. The virus infection was documented in patients from central China and the region that shares the border with North Korea. The clinical manifestations, the time of disease onset, and geographical link of the patient with the region in which the disease is endemic suggest that the patient had SFTS bunyavirus infection.